Regulating the performance of polybenzoxazine via the regiochemistry of amide substituents. (24th October 2019) - Liu, Jingkai; Cao, Lijun; Dai, Jinyue; Xia, Dasha; Peng, Yunyan; Wang, Shuaipeng; Liu, Yuan; Liu, Xiaoqing
Abstract: A new strategy for the property regulation of polybenzoxazine via the regiochemistry of amide substituents was reported in this work. After the benzoxazine isomers, 2, 6BAP-abz and 3, 5BAP-abz, were synthesized, their chemical structures were confirmed by NMR, FT-IR and MS spectra. Then, how does the regiochemistry of amide substituent regulate the curing behaviors of benzoxazine monomers, as well as the thermal properties and flame retardancy of cured resins, poly(2, 6BAP-abz) and poly(3, 5BAP-abz), were investigated. Results showed that the intramolecular H-bonding involved with the ortho-CON H and O in oxazine ring in 3, 5BAP-abz was much stronger than that in 2, 6BAP-abz, which was responsible for its higher curing reactivity. As for the cured resin, poly(2, 6BAP-abz) demonstrated higher glass transition temperature ( T g ) and lower surface free energy (SFE) due to the formation of more intramolecular N–H⋯N interaction between pyridine and ortho-CON H . In addition, this H-bonding was also related with the oxazole ring formation temperature and fire retardancy of poly(2, 6BAP-abz) and poly(3, 5BAP-abz). Overall, a deeper insight into the effect of regiochemistry on properties of polybenzoxazine was achieved. Graphical abstract: Image 1 Highlights: Selective formation of inter- or intramolecular H-bonding in PBZ was achieved through the benzoxazine isomers design. Manipulation on the regiochemistry of amide substituent and its effect on the properties of PBZ were investigated. It is the first time the effect of H-bonding on the polybenzoxazole formation temperature from o-amide PBZ was reported. H-bonding was proved to have relationship with the fire resistance of o-amide PBZ due to the formation of polybenzoxazole.